Analysis of Cyanide Acid in Bamboo Shoots Originating from Polewali Mandar Regency (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Background: Bamboo shoots are a food source derived from young shoots of bamboo plants. While bamboo shoots contain various nutrients, vitamins, minerals, and antioxidants such as polyphenols and flavonoids, they also contain cyanide acid which poses health risks when consumed continuously. Objective: This research aims to determine the levels of cyanide acid in bamboo shoots after boiling for different time durations. Methods: This experimental laboratory study was conducted using UV-Vis spectrophotometry method. Bamboo shoot samples from Polewali Mandar Regency were analyzed for cyanide content before treatment and after boiling for 5, 10, and 15 minutes. Results: The research revealed varying cyanide acid levels: untreated samples (TP) contained 0.396 μg/g, samples boiled for 5 minutes contained 0.226 μg/g, samples boiled for 10 minutes contained 0.232 μg/g, and samples boiled for 15 minutes contained 0.234 μg/g. The highest reduction in cyanide acid levels was achieved through 5-minute boiling, resulting in 0.226 μg/g. Conclusion: Boiling process effectively reduces cyanide acid content in bamboo shoots, with optimal reduction occurring at 5 minutes of boiling time.